Downregulation of miR-146a Contributes to Cardiac Dysfunction Induced by the Tyrosine Kinase Inhibitor Sunitinib - Shen, Li; Li, Congxin; Zhang, Hua; Qiu, Suhua; Fu, Tian; Xu, Yanfang (Frontiers in Pharmacology, 2019)
The main adverse effect of tyrosine kinase inhibitors such as sunitinib is cardiac contractile dysfunction, but the molecular mechanisms remain largely obscure. MicroRNAs (miRNAs) are key regulatory factors in both cardiovascular diseases and the tyrosine kinase pathway. Therefore, we analyzed the differential expression of miRNAs in the myocardium after exposure to sunitinib in mice using miRNA microarray. A significant downregulation of miR-146a was observed in myocardium from sunitinib-treated mice, concomitantly with a 20% decrease in left ventricle ejection fraction (LVEF). The downregulation of miR-146a was further validated by RT-qPCR. Among the potential targets of miR-146a, we focused on Pln and Ank2, which are closely related to cardiac contractile dysfunction. A luciferase reporter assay confirmed that miR-146a directly targets the 3 'untranslated region of Pln and Ank2. Significant upregulation of PLN and ANK2 both at mRNA and protein levels was found in myocardium from sunitinib-treated mice. Cardiac-specific overexpression of miR-146a through AAV9 (adeno-associated virus serotype 9)-mediated gene delivery protect against the decrease of LVEF in sunitinib-treated mice, along with evident recovery in the expression levels of both PLN and ANK2. Moreover, MiR-146a overexpression significantly alleviated the decreased contractility of human induced pluripotent stem cell-derived cardiomyocytes in vitro. Therefore, our results from in vivo and in vitro demonstrate that sunitinib downregulates miR-146a, which contributes to cardiac contractile dysfunction through downstream targets, PLN and ANK2; and upregulation of miR-146a alleviates the inhibition of SNT on cardiac contractility. Thus, miR-146a could be a useful agent for protection against sunitinib-induced cardiac dysfunction.